Cover Image. Issue 3 (8th July 2019) - Fujiwara, Yuki; Eguchi, Shunsuke; Murayama, Hiroki; Takahashi, Yuri; Toda, Mitsutoshi; Imai, Kota; Tsuda, Kinsuke
Abstract : Cover caption The cover image, by Yuki Fujiwara et al., is based on the Original Article Relationship between diet/exercise and pharmacotherapy to enhance the GLP‐1 levels in type 2 diabetes . DOI: 10.1002/edm2.68 .